Peasant organization in coffee communities: La Sombra Chiconquiaco, Veracruz, Mexico - Hernández-Romero, Oliverio; Zaragoza Martínez, Elena; Estrada-Quiterio, Freddy A.; Álvarez González, Xochitl; Rivera Peña, Rubén; Morales Lormendez, Ignacio (Revista Mexicana de Ciencias Agrícolas, 2017)
This investigation notes explores the various forms  of association and organization that peasants working  on coffee have. We discuss the differences between  association and organization and a case study is shown to  identify these concepts. It starts from the conception of  man as an eminently social being, and transiting towards  the characteristics and the constitution of the collective  subjects from the collective consciousness that is formed  when interacting each individual within this social subject.  The concepts of association and organization are open to  discussion based on the basic premise that the association  allows individuals to participate by making decisions  that affect them in their daily lives. And in the case of the  organization, the people who hold power organize the work  of others, i.e., workers or employees, in order to achieve  their own objectives and in the case of the association, the  partners join their individual economic powers, to form a  greater power and to use it in the attainment of its aims. By  the above, a society must be understood as an association,  while an organization must be understood as a company.  Understood as an “instrument to establish purposes, to  be constituted as a collective subject and to join forces or  individual powers to form a greater power, sufficient to  relate positively and successfully with other subjects on  the road to the realization of the goals set by the peasants  themselves.
Keywords: association, peasants, organization